Examination the growth of blue green alga, Chroococcus turigidus in different traditional media formulations (Journal of the College of Basic Education, 2022)
Chroococcus turigidus. One-celled, or an association of 2-32 spherical, hemispherical or ovate individuals, either free floating, adhering to submerged substrates, or forming expansions in moist aerial habitats; cell contents homogeneous or granular, not vacuolated, light to bright blue-green, olive-green, or yellowish. Chroococcus one of the members of blue green algae is the richest source of chlorophyll which is widely used as a health food and feed supplement, as well as in the pharmaceutical and cosmetics industry. Chroococcus has been produced commercially in several countries for its use as food and medicinal purpose due to its valuable contents particularly pigments and proteins. The aim of this work is to evaluate the effect of three different traditional inorganic medium such as Chu-10 medium, BG-11 medium, and BG-11 with minerals medium, on the growth of Chroococcus turigidus. The best growth was obtained in BG-11 with minerals medium as compared to other medium